Do generic strategy and productivity help detect corporate retail bankruptcy risk? - Steph Subanidja; Sri Wahyuni; Melda Lestari; Wilfridus B. Elu (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Recently, there have been several retail companies experiencing bankruptcy. Many studies on bankruptcy risk are more seen from the financial performance perspective. Studies on the risk of financial performance are good but it seems too late to detect the risk. So far, no research investigates some antecedents on the risk directly. It is commonly ended in financial performance. This study detects earlier the risk from antecedents of financial performance as an indicator of the risk. The study aims to investigate the effect of generic strategy, as well as productivity, on bankruptcy. The study is causality research. The population is 25 retail companies. With certain criteria, there are 17 companies as a sample. By using SEM and smart-PLS, it can be concluded that cost leadership affects both on productivity and the risk. Then, the differentiation strategy does not affect productivity, but it affects the risk. Furthermore, productivity is eligible as an intervening variable on the risk. Moreover, the strategy and productivity are good but not enough to detect the risk. Therefore, for detecting the risk possibility, it is needed a further research improvement for detecting the risk from a macro and micro perspective comprehensively.
Keywords: G33; M11; M21; M41; L81; 650; differentiation; cost leadership strategy; productivity; bankruptcy risk; retail companies